The experiences of the process of planning, starting and organizing a culturally specific nursing home for Finnish-speaking older persons: a qualitative study - Emina Hadziabdic; Katarina Hjelm (BMC, 2020)
Abstract Background Globally there are growing multicultural and multilingual societies. As a result of extensive international migration, the number of elderly migrants has increased and will further increase in the future. This makes it necessary for elderly healthcare services to meet elderly migrants' healthcare needs concerning language and cultural barriers. To our knowledge, previous research in the area of culturally specific nursing homes for migrant seniors is still limited. Thus, the study aimed to investigate the experiences of planning, starting and organizing a culturally specific nursing home for Finnish-speaking older persons. Methods An explorative qualitative study using both semi-structured individual interviews and focus group interviews as data collection. Thirteen informants were purposively recruited, two from Finnish-speaking association, seven healthcare professionals and two family members. Data were analysed by qualitative content analysis. Results Three categories, each with sub-categories, emerged from the data: 1) Motivation to develop this particular culture-specific nursing home; 2) Organizational issues and 3) Aspirations for the future. The study found that information from policy makers, the localization and activities of the nursing home, having healthcare staff who speak the minority language, organizing the nursing home as a mixture of older members of both the majority and the minority communities, all affected the planning, starting and organization of a culturally specific nursing home. Conclusion This study found that information, localization, activities and language adapted to elderly migrants affected the planning, starting and organization of a culturally specific nursing home for Finnish-speaking older persons. These findings should support the healthcare organization in planning, managing and organizing sustainable nursing home care for older people belonging to a minority in order to attain the aim of person-centered and equal healthcare.